Simulated microgravity alters the expression of cytoskeleton- and ATP-binding-related genes in MLO-Y4 osteocytes. (December 2016) - Chen, Zhihao; Zhao, Fan; Qi, Yiduo; Hu, Lifang; Li, Dijie; Yin, Chong; Su, Peihong; Zhang, Yan; Ma, Jianhua; Qian, Jing; Zhou, Hongpo; Zou, Yiwei; et al.
Abstract: Bone undergoes dynamic modelling and remodelling processes, and it requires gravity-mediated mechanical stimulation for the maintenance of mineral content and structure. Osteocytes are the most commonly found cells in the mature bone, and they are sensitive to mechanical changes. The purpose of this study was to investigate the effects of microgravity simulated with a random position machine (RPM) on the gene expression profile of osteocytes. Genes sensitive to RPM treatment were sorted on the basis of biological processes, interactions and signalling pathways. Overall, 504 differentially expressed genes (DEGs) in osteocytes cultured under RPM conditions were found. The DEGs were further analysed using bioinformatics tools such as DAVID and iReport. A total of 15 ATP-binding and cytoskeleton-related genes were further confirmed by quantitative real-time PCR (qRT-PCR). Our findings demonstrate that the RPM affected the expression of genes involved in cytoskeleton remodelling and the energy-transfer process in osteocytes. The identification of mechanosensitive genes may enhance our understanding of the roles of osteocytes in mechanosensation and may provide some potential targets for preventing and treating bone-related diseases. Highlights: The random position machine (RPM) was used to simulate microgravity. Microgravity affected the gene expression profile of MLO-Y4 osteocytes. Cytoskeleton- and ATP-binding-related genes expression altered under microgravity. Gene-gene interactions of validated genes were analysed.